2009
DOI: 10.1002/chem.200901525
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Agents from the Australian Tropical Rainforest: Spiroacetals EBC‐23, 24, 25, 72, 73, 75 and 76

Abstract: EBC-23, 24, 25, 72, 73, 75 and 76 were isolated from the fruit of Cinnamomum laubatii (family Lauraceae) in the Australian tropical rainforests. EBC-23 (1) was synthesized stereoselectively, in nine linear steps in 8 % overall yield, to confirm the reported relative stereochemistry and determine the absolute stereochemistry. Key to the total synthesis was a series of Tietze-Smith linchpin reactions. The novel spiroacetal structural motif, exemplified by EBC-23 (1), was found to inhibit the growth of the androg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 73 publications
1
29
0
Order By: Relevance
“…Previous work [22] had demonstrated that these epoxides undergo smooth ring opening when reacted with either the anion of dithiane 4a or the TMS-dithane 4b and as such acted as a benchmark to dithiane reactivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work [22] had demonstrated that these epoxides undergo smooth ring opening when reacted with either the anion of dithiane 4a or the TMS-dithane 4b and as such acted as a benchmark to dithiane reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has previously experienced this problematic issue first hand. [22] With a desire to gain a general understanding of AAE reactivity and overcome, or avoid, S-alkylation we searched the literature, which to our surprise unveiled a substantial paucity of work in this area. For example, there were no comparative reactivity studies of known AAEs and no clear understanding or description as to why sulfur was a common functional group element.…”
Section: Introductionmentioning
confidence: 99%
“…The second compound is EBC 23 96, isolated from Cinnamon laubatii, which is an inhibitor of the growth of androgen-independent prostate tumor cells. The preparation of 96 involves a RCM step aided by microwave irradiation [167,168] (Scheme 35).…”
Section: Acrylate-type Ring Closure: Synthesis Of Natural Productsmentioning
confidence: 99%
“…In the most basic test for anticancer activity immortalized cancer cells are grown in a culture and examined for survival or suppression under conditions of the respective treatment [67]. For antioxidant or free radical scavenging activity, a coloured free radical can be reduced by the treatment and made invisible to the naked eye, with the results quantified by a spectrophotometer on the visible spectrum [68].…”
Section: Bioactivity Testingmentioning
confidence: 99%